Perbandingan Kinerja Keuangan Perusahaan Sebelum dan Sesudah Mengakuisisi PT Mulia Boga Raya Tbk pada PT Garuda Food Putra Putri Jaya Tbk Tahun 2018-2022 - Amallia Dwi Puspita; Ahmad Idris; Trisnia Widuri (Master Manajemen, 2025)
In carrying out measurements of the company's financial performance, several types of financial ratios are used, such as profitability, activity, solvency, and liquidity ratios. The purpose of the study is to provide comparative results of the company's financial performance as reviewed from the profitability, activity, solvency, and liquidity ratios before and after acquiring PT Mulia Boga Raya Tbk at PT Garuda Food Putra Putri Jaya Tbk in 2018-2023. The type of research used is quantitative descriptive research. The findings are that the Current Ratio before and after the acquisition is different, but not significant. This acquisition has an optimal impact on increasing the efficiency of the company's current asset management. The company's Debt to Equity Ratio shows the difference before and after the acquisition, but not significant. The acquisition makes a good contribution to the efficiency of the company's current asset management. Return on Equity shows the difference before and after the acquisition, but the change is not significant. The acquisition does not have a significant effect on the efficiency of using equity in generating profits. Total Asset Turn Over experiences an insignificant difference before and after the acquisition.